The The Effect of Administration of Sweet Leaf on Hemoglobin Levels in Pregnant Women with Anemia at Bara-Baraya Health Center, Makassar City - Rahmawati; Mirna; Fadjriah Ohorella; Amina Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Anemia poses a significant health problem in developing countries, particularly among pregnant women who experience a high morbidity rate. Globally, anemia ranks third among pregnant women, with a prevalence rate of 74%. The primary causes of anemia cases are iron deficiency and acute bleeding, which interact with each other.This study employed an experimental research design known as quasi-experimental. The treatment or intervention was administered to the respondents who were divided into two groups: the control group, which did not receive the treatment, and the intervention group, which did. Prior to the intervention, both groups underwent an initial examination. Subsequently, the intervention group was given sweet potato leaf decoction, followed by a post-administration examination.The results obtained from the SPSS test demonstrated significant changes in hemoglobin levels among 15 respondents in the intervention and control groups. The test yielded a p-value of 0.000, with p < α (α < 0.005), indicating a significant alteration in hemoglobin levels before and after administering sweet potato leaves to pregnant women with anemia. Moreover, the independent test revealed a p-value of 0.005, with (α < 0.005), highlighting a significant difference between the intervention and control groups. This research endeavor aims to enhance knowledge and comprehension regarding the benefits of sweet potato leaves, particularly for healthcare professionals. Sweet potato leaves serve as a viable alternative in increasing hemoglobin levels among pregnant women with anemia.